(untitled) (Conferencea, 2022)
In Uzbekistan, along with the rapid development of our republic, the demand for high-quality fuels is increasing. This requires the effective use of new technologies in line with global standards. The article examines the production of diesel fuel from gas condensate and its quality indicators.